AKTIVITAS DIURETIK EKSTRAK ETANOL BIJI ALPUKAT (Persea americana Mill.) - Khairun Nida; Purnama Fajri; Harpolia Cartika; Fatwa Hasbi (JURNAL KATALISATOR, 2022)
Previous research conducted by Omodamiro and Jimoh showed that the ethanol seed extract of Persea americana , known as avocado had a diuretic activity of urine volume and electrolytes Na+, Cl- and K+ which increased significantly compare to the normal control group. Thus it is necessary to conduct further research on the ethanol seed extract of avocado to determine wether increasing dose of the extract can increase the diuretic activity. The aim of the study was to determine diuretic profile of the ethanol seed extract of avocado against furosemide as appositive control. Testing of diuretic activity uses the parameter of urine volume excreted every 30 minutes for 6 hours and 24 hours. Three treatment groups containing extracts of 7 mg, 14 mg, 28 mg were compared to furosemide.     The three doses of this extract had a diuretic profile that was not identical to that of furosemide, but had the same diuretic activity with the significant value (p> 0,05). A dose of 28 mg has a better diuretic effect than furosemide, which is characterized by the accumulation of a higher volume of urine produced. This means that the higher the dose, the better the diuretic activity